Position-dependent Effects of Polylysine on Sec Protein Transport - Liang, Fu-Cheng (American Society for Biochemistry and Molecular Biology, 2012)
The bacterial Sec protein translocation system catalyzes the transport of unfolded precursor proteins across the cytoplasmic membrane. Using a recently developed real time fluorescence-based transport assay, the effects of the number and distribution of positive charges on the transport time and transport efficiency of proOmpA were examined. As expected, an increase in the number of lysine residues generally increased transport time and decreased transport efficiency. However, the observed effects were highly dependent on the polylysine position in the mature domain. In addition, a string of consecutive positive charges generally had a more significant effect on transport time and efficiency than separating the charges into two or more charged segments. Thirty positive charges distributed throughout the mature domain resulted in effects similar to 10 consecutive charges near the N terminus of the mature domain. These data support a model in which the local effects of positive charge on the translocation kinetics dominate over total thermodynamic constraints. The rapid translocation kinetics of some highly charged proOmpA mutants suggest that the charge is partially shielded from the electric field gradient during transport, possibly by the co-migration of counter ions. The transport times of precursors with multiple positively charged sequences, or “pause sites,” were fairly well predicted by a local effect model. However, the kinetic profile predicted by this local effect model was not observed. Instead, the transport kinetics observed for precursors with multiple polylysine segments support a model in which translocation through the SecYEG pore is not the rate-limiting step of transport.